Determinants of Nursing Process Implementation in North East Ethiopia: Cross-Sectional Study - Yihun Miskir; Solomon Emishaw (Hindawi Limited, 2018)
Nursing process is a framework used to provide an effective, coordinated, and organized quality care for patients. Effective implementation of this framework leads to improved quality of care and decreases potential complication, hospital length of stay, and the cost of care. To assess implementation of nursing process and its hindering factors, a quantitative cross-sectional study was conducted among nurses in Afar region hospitals from October 2016 to December 2016. The data were collected from 102 nurses using primary Brooking's ward nurses' self-report questionnaire and with some newly prepared questions. The collected data were entered using Epi-Data version 3.1 and analyzed by SPSS version 20 and then presented by tables, graphs, and figures. Forty-three (42.1%) nurses were implementing nursing process at the time of data collection. Assessment and diagnosis were carried out by 57 (56.9%) nurses, planning by 46% of nurses, implementation by 38.2% of nurses, and evaluation by 36.2% of nurses in Afar region. Among the hindering factors towards nursing process implementation, lack of preparedness or knowledge about the nursing process or some part of it (83.3%) and absence of in-service training pertinent to nursing process (75.5%) were the most mentioned ones. Generally, nursing process was poorly implemented in Afar region mainly due to lack of knowledge and absence of in service training. Therefore, giving emphasis for cognitive parts of students about nursing process during their school time and refreshing nurse staffs with continuous training will definitively improve level of nursing process implementation.